Facial Plastic Surgery Faculty Turnover: Survey of Academic Facial Plastic Surgeons and Department Chairs - Kowalczyk, David Michael; Jordan, J Randall (International Archives of Otorhinolaryngology, 2019)
Introduction The turnover and inability to consistently retain academic facial plastic surgeons is an issue that many academic departments of otolaryngology face. In addition to the financial costs of staff turnover and gaps in patient care, insufficient exposure of residents to key surgical procedures is a significant problem for residency programs.Objective To identify the most important reasons that lead faculty members to leave an academic facial plastic surgery (FPS) practice as well as features that may be associated with retention of FPS faculty.Methods Members of the American Academy of Facial Plastic and Reconstructive Surgery (AAFPRS) and the Association of Academic Departments of Otolaryngology (AADO) were administered an anonymous, online survey. For both groups, we evaluated demographic factors, reasons for choosing academic careers, contributors to faculty turnover, as well as strategies for retention. The frequency of the responses was analyzed.Results A total of 11.3% (135/1,200) of facial plastic surgery faculty responded to the faculty survey, with 59.1% (68/115) of current, academic surgeons participating, and a total of 16.7% (20/120) of department chairs responded to the chairs' survey. If a faculty member had left/was to leave, more control over practice was the most common reason between the two respondent groups. Of the five most important ways to increase faculty retention, more control over practice was the number one reason.Conclusion Chairs and facial plastic surgery faculty should strive to agree upon the amount of control over the academic practice to lead to higher retention, better patient care, and continued resident education.
Keywords: plastic surgery; surveys and questionnaires; otolaryngology